The Connection Between the Activity Within the Social Networks and The Consumer Behaviour - New Techniques for Knowing the Consumer Behaviour - Raluca-Giorgiana (POPA) CHIVU; Ionuț-Claudiu POPA; Bianca Cristiana VOICU; Ionuț TĂNASE (Communications of International Proceedings, 2022)
Buying and consuming behaviour has been a broad topic studied by marketers out of a desire to know and satisfy the needs and desires of consumers. From the beginning of marketing, different research methods have been used, from gathering information through questionnaires and interview guides to marketing experiments and focus groups, in order to know their desires and needs, but also analyzing the determinants of their decisions (grouped generically in the form of endogenous and exogenous factors influencing consumer behaviour). These identified influencing factors are still valid today, but their research and identification methods have evolved with technological developments. The emergence of social networks, for example, is a first step in using new methods of gathering information about consumers, indicating their current needs and desires. The advantages of using the information within the social networks are numerous, being highlighted first of all their actuality (behavioural or decisional changes can be observed in real-time) and the reduced costs (both in terms of human and financial resources and time). In this article, using a series of theoretical information on consumer psychology and behaviour in the online environment, a study was developed on the links between endogenous and exogenous factors influencing consumer behaviour and their activities in the online environment in order to highlight the usefulness of analyzing information within social networks as a research tool in marketing.
Keywords: social media intelligence; consumer behaviour; marketing research.